RANCANG BANGUN MESIN PENGGILING UBI PEMBUAT GETUK DENGAN SILINDER ULIR KAPASITAS 50 KG/JAM - Pandiangan, Prabu J.G; Oppusunggu, K (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2017)
At present the yam milling is still a lot of using manual methods, namely by pounding yams using mortar, where this work takes a long time so that the required results are not maximal. So to simplify and shorten the processing of yam mills, a yam grinding machine is made with the aim to speed up the work and get maximum results so that it can meet the needs of the market. This sweet potato grinding machine is a tool to grind yams in an automatic way that can be used as needed, so that the work can be completed quickly. This engine is driven with 1 hp and 1450 rpm rotation, forwarded to a drive pulley that is 4 inches in diameter, and a 6 inch pully driven, as a round connector used a V. type belt. This 4 inch diameter will move a reducer with a rotation ratio of 1 : 40 then forwarded to the drive shaft, the shaft used is 30 mm in diameter, where the shaft used is the shaft shafts. The threaded shaft is made of stainless steel, and at the end of the shaft there are 4 pieces of knife blade which are used to chop up unripe yam fibers. Machine frame material from steel elbow plate (propil